FACTORS LEADING TO PERINEAL INJURY DURING VAGINAL DELIVERY (The Research of Medical Science Review, 2025)
Objective: To evaluate the labour characteristics and other predictors of perineal injury in women delivering at a tertiary care hospital.Place and Duration of Study: Conducted at Department of Obstetrics and Gynaecology AIMS Hospital Muzaffarabad for six months after approval of synopsis.Study Design: A cross-sectional analytical study.Methodology: A total of 311 women who delivered vaginally were included. Labour duration was categorized into <6 hours, 6–12 hours, and >12 hours. The primary outcome was the occurrence of perineal injury. Unadjusted and adjusted odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using logistic regression to determine the association between labour characteristics and perineal injury. Statistical significance was set at p<0.05.Results: Perineal injury occurred in 107 (34.4%) women. Labour duration was significantly associated with perineal injury (p=0.002). Women with labour lasting 6–12 hours had an increased risk of perineal injury (Adjusted OR: 2.38, 95% CI: 1.30–4.37) compared to those with labour <6 hours. The highest risk was observed in women with labour >12 hours (Adjusted OR: 5.67, 95% CI: 2.76–11.7). Other significant predictors included primiparity and instrumental delivery.Conclusion: Long duration of labour was significantly associated with higher risk of perineal injury. Risk factors for obstetrical anal sphincter tears include the following; identifying these women and implementing preventative strategies including perineal support techniques and controlled delivery may reduce morbidity. More studies are needed to investigate other contributing factors in other obstetric populations.